PENGARUH BIMBINGAN MANAJEMEN DIRI DALAM MENINGKATKAN KEDISIPLINAN BELAJAR SISWA - Titi Mirawati Asim (Journal of Educational Science and Technology (EST), 2016)
The study was helt in atirah I senior high school grade XI at Makassar city the purpose is to know (1) the process and results of implementation of self management guidance in improving learning discipline experimental group students of. (2)  the level of learnig discipline to learn the experimental group before and after the self-management guidance services. (3) the level of learning discipline of the control group before and after teach by giving information about the desciplane. (4) whether there are differences between the application of self-management guidance and information services in improving the efficientcy of learn discipline. This research uses and experimental approach (True Experimental Designs) in the form of pretest-posttest control group design. This study used data collection techniques by questionnaires, observation and evaluation of the understanding. Data analysis using descriptive statistical analysis of Wilcoxon signed ranks test. The results of this study indicate (1) The process of experimentel was running well. (2) level of discipline studying students before the experimental group was given self-management guidance services that are in the low category, while the level of discipline to learn the experimental group of students after being given self-management guidance services are in high category. (3) The level of discipline to learn the control group before and after teacing through  information services remain at a low category, (4) there is a difference in learning discipline of experiental group student which giving self management guidance, and control groub students which giving information services